Kavalactones support motivation to move during intensive training in males preparing for military special operations forces - Sheena Y. Smith; Carlos F. Aylwin; Tyler F. Daniels; Jennifer L. Greer; Laura J. Kunces; Loukia Lili; Stephen M. Phipps; Caleb M. Schmidt; Julian C. Schmidt; Michael A. Schmidt (Journal of the International Society of Sports Nutrition, 2024)
Background Military special operators, elite athletes, and others requiring uninterrupted optimal performance currently lack options for sleep and mood support without performance-inhibiting effects. Kavalactones, derived from the root of the kava plant (Piper methysticum Forst), have been shown to elevate mood and wellbeing by producing a feeling of relaxation without addiction or cognitive impairment.Methods In this placebo-controlled, crossover study (NCT05381025), we investigated the effects of 2 weeks of kavalactones use on cortisol (diurnal salivary), sleep (RSQ-W; Restorative Sleep Questionnaire, Weekly), mood (DASS-21; Depression Anxiety Stress Scale-21), and motivation state to expend (Move) or conserve (Rest) energy (CRAVE; Cravings for Rest and Volitional Energy Expenditure, Right Now) in a cohort of 15 healthy, physically fit young males engaged in a rigorous, two-a-day preparation class for special operations forces qualification.Results Cortisol, sleep, and mood were within normal, healthy parameters in this cohort at baseline. This remained unchanged with kavalactones use with no significant findings of clinical interest. However, a statistically similar, positive slope for within-group Move scores was seen in both groups during kavalactones loading (first group Move slope 2.25, second group Move slope 3.29, p = 0.299). This trend was seen regardless of order and with no apparent effects on the Rest metric (all p ≥ 0.05). Moreover, a significant between-group difference appeared after 1 week of kavalactones use in the first phase (p = 0.044) and persisted through the end of the first loading period (p = 0.022). Following the 10-day washout, this between-groups divergence remained significant (p = 0.038) but was reversed by 1 week after the crossover (p = 0.072), with Move scores once again statistically similar between groups and compared to baseline at study end. Furthermore, the group taking kavalactones first never experienced a significant decrease in Move motivation state (lowest mean score 21.0, highest 28.6, all p ≥ 0.05), while the group receiving kavalactones in the last 2 weeks of the study had Move scores that were statistically lower than baseline (lowest mean score 8.6, highest 25.9, all p ≤ 0.05) at all time points but the last (p = 0.063) after 2 weeks of kavalactones exposure.Conclusions We report a novel finding that kavalactones may support performance by maintaining or rescuing the desire to expend energy in the context of significant physical and mental strain in well-conditioned individuals, even in a context of already normal cortisol, sleep, and mood.